2022
DOI: 10.1097/brs.0000000000004517
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hounsfield Units and Severe Multifidus Sarcopenia Are Independent Predictors of Increased Risk for Proximal Junctional Kyphosis and Failure Following Thoracolumbar Fusion

Abstract: Study Design. Retrospective cohort study.Objective. The purpose of the present study was to assess the impact of sarcopenia on the development of proximal junctional kyphosis (PJK) and proximal junctional failure (PJF) following thoracolumbar spine fusion surgery using opportunistic evaluation of paraspinal fatty degeneration on preoperative magnetic resonance imaging. Summary of Background Data. While paraspinal sarcopenia has been shown to have detrimental consequences following posterior cervicothoracic fus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…40 While cross-sectional measurements are simple to perform on readily available preoperative advanced imaging studies, subsequent studies have demonstrated that cross-sectional area measurements do not correlate with qualitative assessments of paraspinal fatty infiltration and are not reliably tied to outcomes following spine surgery, leading to the recommendation that qualitative assessments be used preferentially. 22,24,41 Koshimizu et al investigated 171 patients undergoing laminoplasty and found that sarcopenic patients, as determined by appendicular skeletal muscle mass, had lower Japanese Orthopedic Association scores, higher C2-7 sagittal vertical axis measurements, and lower short form-36 scores. 14 While these findings highlight the impact of sarcopenia on postoperative outcomes, appendicular skeletal muscle index is determined using dual-energy x-ray absorptiometry, which is not part of routine preoperative testing and only serves as a proxy for paraspinal sarcopenia rather than as a direct measurement of the quality of the muscles of interest.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…40 While cross-sectional measurements are simple to perform on readily available preoperative advanced imaging studies, subsequent studies have demonstrated that cross-sectional area measurements do not correlate with qualitative assessments of paraspinal fatty infiltration and are not reliably tied to outcomes following spine surgery, leading to the recommendation that qualitative assessments be used preferentially. 22,24,41 Koshimizu et al investigated 171 patients undergoing laminoplasty and found that sarcopenic patients, as determined by appendicular skeletal muscle mass, had lower Japanese Orthopedic Association scores, higher C2-7 sagittal vertical axis measurements, and lower short form-36 scores. 14 While these findings highlight the impact of sarcopenia on postoperative outcomes, appendicular skeletal muscle index is determined using dual-energy x-ray absorptiometry, which is not part of routine preoperative testing and only serves as a proxy for paraspinal sarcopenia rather than as a direct measurement of the quality of the muscles of interest.…”
Section: Discussionmentioning
confidence: 99%
“…In their study of 144 patients undergoing cervical laminoplasty for DCM, Lee et al reported that decreased cross-sectional area of the semispinalis cervicis at C5-6 on advanced preoperative imaging was associated with loss of cervical lordosis postoperatively 40. While cross-sectional measurements are simple to perform on readily available preoperative advanced imaging studies, subsequent studies have demonstrated that cross-sectional area measurements do not correlate with qualitative assessments of paraspinal fatty infiltration and are not reliably tied to outcomes following spine surgery, leading to the recommendation that qualitative assessments be used preferentially 22,24,41. Koshimizu et al investigated 171 patients undergoing laminoplasty and found that sarcopenic patients, as determined by appendicular skeletal muscle mass, had lower Japanese Orthopedic Association scores, higher C2-7 sagittal vertical axis measurements, and lower short form-36 scores 14.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients undergoing multilevel thoracolumbar fusions with multifidus fatty degeneration and decreased lean multifidus CSA have been shown to independently predict rates of PJK and PJF on multivariate analyses. 39,40 In the case of smaller fusion constructs, evidence demonstrates the value of radiographic evidence of paraspinal sarcopenia. In 1 study of patients undergoing 2 or more level fusions extending caudally into the sacrum, paraspinal muscle markers (lean CSA, FI, and SMI) at the UIV were more predictive of ASD as opposed to signs of psoas degeneration.…”
Section: Proximal Junctional Kyphosis and Failure In Lumbar Surgerymentioning
confidence: 99%